Conceptualizing 'role' in patient-engaging e-health: A cross-disciplinary review of the literature. (9th September 2016) - Langstrup, Henriette; Rahbek, Anja
Abstract : Patient-engaging eHealth is promoted as a means to improve care and change the social order of healthcare – most notably the roles of patients and healthcare professionals. Nevertheless, while researchers across various fields expect and praise such changes, these social aspects are rarely addressed rigorously in the literature on the effects of eHealth. In this paper we review the scientific literature on patient-engaging eHealth with the purpose of articulating the different ways in which role is conceptualized in the different strands of literature and what explicit and implicit assumptions such conceptualizations entail. We identify three different conceptualizations of the concept of role and exemplify the findings proposed by the studies that apply each of the three conceptualizations. We hereby argue that such conceptual differences have implications for what is found to be at stake when using eHealth to further the involvement of patients in their own care. We argue that a more rigorous and reflective approach to the use of concepts with rich intellectual histories such as the concept of role will qualify both empirical research in eHealth as well as discussions of implications for practice.